2017
DOI: 10.15343/0104-7809.20174103385394
|View full text |Cite
|
Sign up to set email alerts
|

Palliative extubation: case analysis in an Intensive Care Unit

Abstract: Current technological advancements have allowed for the prolongation of the dying process, especially in Intensive Care Units (ICU). This has increased the need for decisions on the limitation of therapeutic effort (LTE), such as the use of palliative extubation that, although difficult from an emotional standpoint, has legal and ethical justifications, and has increased family acceptance. The objective was to evaluate the clinical and demographical profile of patients submitted to palliative extubation (PT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Most family members would likely prefer the choice to shorten the dying process of the patients by withdrawing the ventilator 18 . In Brazil, however, palliative extubation is seldom performed 3 5 : 50.2% of Brazilian intensivists admit fear of litigation, although over 75% claim to have received specific palliative care training 19 . A survey 20 collected responses from 105 ICU physicians in Brazil in 2012 regarding a case vignette of a critically ill patient with post-cardiac arrest encephalopathy and sepsis: none would perform palliative extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Most family members would likely prefer the choice to shorten the dying process of the patients by withdrawing the ventilator 18 . In Brazil, however, palliative extubation is seldom performed 3 5 : 50.2% of Brazilian intensivists admit fear of litigation, although over 75% claim to have received specific palliative care training 19 . A survey 20 collected responses from 105 ICU physicians in Brazil in 2012 regarding a case vignette of a critically ill patient with post-cardiac arrest encephalopathy and sepsis: none would perform palliative extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo estudo realizado na unidade de terapia intensiva (UTI) de um Hospital Universitário, grande parte dos pacientes, que foram submetidos à extubação paliativa, é de idosos, acometidos por doenças neurológicas, tendo como tempo de vida pós-procedimento variável de minutos a dias, porém sua maioria foi a óbito após 24 horas. Rebelatto e Moritz 22 pós-extubação está relacionado à gravidade da doença, e não à retirada do suporte ventilatório. Já subsequente a este estudo, em outra pesquisa, observou-se que grande parte dos pacientes analisados foi a óbito no local onde foi realizada a extubação paliativa, no próprio hospital.…”
Section: Discussionunclassified
“…The statements showed that oncology ICU professionals were familiar with the concept of palliative extubation, as described in the literature. It involves removing the invasive mechanical ventilator in the face of an irreversible clinical condition, with the aim of promoting comfort and relief for the patient, allowing the disease to take its natural course [1][2][3][4][6][7][8][9][10][11] .…”
Section: Characterization Of Palliative Extubationmentioning
confidence: 99%
“…As the literature itself points out, professionals still associate the dyspneic patient's well-being with the provision of oxygen support or invasive ventilation; or they relate palliative extubation to shortening the patient's life span and inducing death, often making difficult an effective communication between team members themselves and with the family 2,5,10,13,19 .…”
Section: Conflicting Feelings About Palliative Extubationmentioning
confidence: 99%
See 1 more Smart Citation